Authentic Leadership and Team Performance: Exploring the Mediating Role of Dynamic Adaptive Capability - Sumarmi, Saptaningsih; Tjahjono, Heru Kurnianto; Qamari, Ika Nurul; Shaikh, Mohsin (Journal of Leadership in Organizations, 2024)
Introduction/Main Objectives: This research explores Dynamic Adaptive Capability to achieve Team Performance in higher education institutions, focusing on the challenges posed by a rapidly changing global environment. The study emphasizes the importance of dynamic adaptability as a mediating variable, connecting Authentic Leadership and Justice Climate as key elements influencing Team Performance. Background Problems: The main question of this research is whether Authentic Leadership improves Team Performance through Dynamic Adaptive Capability. The urgency of this research in Indonesia's higher education context is critical, considering that the ever-changing global environment demands rapid and effective adaptation to remain competitive and relevant. Novelty: Empirical evidence explaining how Authentic Leadership can improve Team Performance in Indonesian higher education still needs to be explored. Therefore, research that finds this mechanism is still required and adds Dynamic Adaptive Capability as a mediator. Research Methods: This research collected a survey of the Head of the Study Program as a team representative, used purposive sampling, and utilized AMOS SEM analysis to test the hypothesis. Finding/Results: The research shows that Authentic Leadership positively impacts Dynamic Adaptive Capability and Team Performance. Meanwhile, Justice Climate has no relationship with Team Performance but positively impacts Dynamic Adaptive Capability. Dynamic Adaptive Capability positively mediates Authentic Leadership and Team Performance while negatively mediating Justice Climate and Team Performance. Conclusion: In addition to supporting several hypotheses, this research also highlights the complex and diverse nature of these relationships, prompting recommendations for strategic planning and further investigation to deepen our understanding of the dynamics in organizational environments.